PENGARUH PEMBERIAN PUPUK MIKRO ORGANISME LOKAL (MOL) TERHADAP PERTUMBUHAN BIBIT JABON (Antochephalus cadamba) - Andilau Andilau; M. Mardhiansyah; Evi Sribudiani (JURNAL ILMU-ILMU KEHUTANAN, 2019)
Antochephalus cadamba is a local Indonesian plant that grows very fast and can thrive in tropical forests. Good quality Antochephalus cadamba seeds are needed to make sure the success of the planter and good results. Local Micro Organism (LMO) is a solution of the decay of organic materials derived from plant residues, animal feces, and humans, which contain more than one element. Local Micro Organisms are micro-organisms that are used as starters in making solid organic fertilizers and liquid fertilizers. The aim of the study was to find the effect of Local Micro Organism fertilizer on the growth of Antochephalus cadamba seedlings and the best dose of LMO fertilizer to trigger the growth of seedlings. This research was carried out with an experimental method using a non factorial Completely Randomized Design, LMO fertilizer consisting of five treatments with four replications, to get twenty experimental units. The results that the application of LMO fertilizer on the growth of Antochephalus cadamba dose is best 60 cc/plant, by showing the result of 100% percent of life seedling, growt of plant height is 15,03 cm and dry weight of plant is 35,11 g.